The Effect of Summarizing Narrative Texts to Improve Reading Comprehension - Maria Rossana Ramirez-Avila; Jahaira Paola Barreiro (Universitas Muhammadiyah Yogyakarta, 2021)
This study demonstrates the effect of summaries of narrative texts to improve reading comprehension. This study consisted of sixty elementary school students who had evident reading comprehension deficiencies, especially in narrative texts. This study is a pre-experimental study with a mixed design. Qualitative and quantitative instruments were applied to meet the purpose of this study. The instruments included pretest and post-test, rubric, learning log, survey, a checklist to measure the students’ development and progress, and their perspectives towards this innovation. Results indicated an improvement in students’ reading comprehension. Post-test means increased from 5.96 in the pretest to 9.10. The checklist also proved that students included the required elements in their summaries. Students indicated in the learning logs that they would extend this strategy to other subjects, and they had to reread and identify the most crucial information to summarize. The study has implications for teachers and learners since it can bring positive considerations about the importance of using summaries to improve reading comprehension.